Jawabanmu

2014-03-03T15:13:13+07:00
Ax + b = 0

f(x) oleh x + 2 ⇒ f(-2) 
f(x) oleh 2x-1 ⇒ f(1/2) 

f(-2) = ax + b = 4    ⇒     -2a + b = 4
f(1/2) = ax + b = 6  ⇒     1/2a + b = 6

Hasil eleminasi    ⇒        -5/2a   =  -2
                                                    a   = 4/5 
                                 ⇒       -2a + b = 4
                                            -2(4/5) + b = 4
                                            -8/5 + b      = 4
                                                        b      = 20/5 + 8/5 
                                                        b      = 28/5 
Sisa ⇒ ax + b 
              4/5x + 28/5 = 4x + 28
Mohon di cek ulang ya< siapa tw ada slh itung :D